Hubungan Gaya Kepemimpinan Kepala Ruangan Terhadap Kepuasan Kerja Perawat Di Ruang Rawat Inap Akasia Dan Cendana Rumah Sakit Dr. Bratanata Kota Jambi - Harnika Harnika; Yusnilawati Yusnilawati; Indah Mawarti (Jurnal Medika Nusantara, 2023)
One of the causes of nurse job satisfaction is influenced by leadership style factors. Nurses who are satisfied with their jobs tend to provide better and more effective care to patients. This has a positive impact on patient satisfaction and trust in the hospital. Quantitative research with the type of associative analysis research using Cross Sectional. Sampling using the Total Sampling approach totaling 36 nurses in the acacia and sandalwood rooms. Data analysis using the chi square test. 1)The optimal autocratic leadership style is 38.9%; 2)optimal democratic 72.2%; 3) optimal free control of 33.3%; 4) Nurse job satisfaction has a satisfied category of 58.3%; 5) There is a significant relationship between the autocratic leadership style and the job satisfaction of nurses with a p-value = 0.000; 6) democratic leadership style with a p-value = 0.000; 7) free control leadership style with a p-value = 0.040. There is a significant relationship between autocratic, democratic, and free control leadership styles on the job satisfaction of nurses at Dr. Hospital. Jambi City Bratanata. It is recommended for the head of the room to have clear and continuous communication with the nurse in order to build a strong relationship between the leader and the nurse. Give nurses the opportunity to make decisions and take responsibility for their work.